What the radiologist should know about postoperative MDCT evaluation of a patient treated with cytoreductive surgery with or without hyperthermic intraperitoneal chemotherapy. Issue 6 (June 2018) - Durot, C.; Rousset, P.; Thivolet, A.; Passot, G.; Deguelte, S.; Dohan, A.; Glehen, O.; Hoeffel, C.
Abstract : Cytoreductive surgery (CRS), often associated with hyperthermic intraperitoneal chemotherapy (HIPEC), is now a well-recognised treatment for most peritoneal malignancies in selected patients. As imaging is frequently performed postoperatively, radiologists are increasingly confronted with postoperative multidetector-row computed tomography (MDCT) examinations in these cases. In this article, after briefly describing the procedures that are currently being performed for the treatment of peritoneal metastases, the normal postoperative MDCT changes that may be encountered after these procedures are described. We then highlight complications that may arise after CRS, depending on the surgery performed, and those related to HIPEC, and illustrate their MDCT features.